2017
DOI: 10.1093/ofid/ofx018
|View full text |Cite
|
Sign up to set email alerts
|

Community Environmental Contamination of Toxigenic Clostridium difficile

Abstract: Background. Clostridium difficile infection is often considered to result from recent acquisition of a C difficile isolate in a healthcare setting. However, C difficile spores can persist for long periods of time, suggesting a potentially large community environmental reservoir. The objectives of this study were to assess community environmental contamination of toxigenic C difficile and to assess strain distribution in environmental versus clinical isolates.Methods.From 2013 to 2015, we collected community en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 24 publications
7
34
0
1
Order By: Relevance
“…Clostridium difficile is widespread outside hospitals and can be isolated from nearly any environment (Alam et al., ). The importance of non‐hospital reservoirs was demonstrated in a large surveillance study showing that almost half (45%) of clinical C. difficile isolates were not consistent with the nosocomial acquisition and that a large environmental reservoir is the most likely source of these isolates (Eyre et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium difficile is widespread outside hospitals and can be isolated from nearly any environment (Alam et al., ). The importance of non‐hospital reservoirs was demonstrated in a large surveillance study showing that almost half (45%) of clinical C. difficile isolates were not consistent with the nosocomial acquisition and that a large environmental reservoir is the most likely source of these isolates (Eyre et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic C. difficile colonies were tested using latex agglutination reagent (Oxoid, Hampshire, England) and presence of triose phosphate isomerase and toxin genes was determined using multiplex PCR [22]. Fluorescent PCR ribotyping was performed as previously described [23]. This technique does not distinguish between all ribotypes; therefore, some ribotypes are reported as combined (e.g.…”
Section: Collection Culture and Typingmentioning
confidence: 99%
“…We have previously demonstrated that toxigenic C. difficile spores are present in the healthcare and non–healthcare environments, including shoe bottoms. 2 It is possible that sites that underwent terminal cleaning became recontaminated from another source. This example demonstrates the value of typing in addition to culture to demonstrate removal of the original clone.…”
Section: Discussionmentioning
confidence: 99%
“…2 From each sample, 10mL broth culture was centrifuged to concentrate the cells with the resulting pellet suspended in 100 μL of normal saline (0.85% NaCl), plated onto cycloserine cefoxitin fructose agar (CCFA, Anaerobic Systems, Morgan Hill, CA), and incubated anaerobically at 37°C for 40–48 hours (Forma Anaerobic System, Mode 1025/1029). Suspected colonies were tested using latex agglutination reagent (Oxoid, Hampshire, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation